2017
DOI: 10.18869/acadpub.ijree.2.2.10
|View full text |Cite
|
Sign up to set email alerts
|

corrective feedback, educational context, Iranian EFL teachers

Abstract: This study investigated the possible relationship between educational context and English Language Teaching (ELT) teachers' corrective feedback preference. To this end, 42 Iranian EEFL teachers from some private language institutes and 39 Iranian EFL teachers from different schools in Shiraz, Iran participated in the study. The Questionnaire for Corrective Feedback Approaches (QCFAs) was used as the instrument in this study. The questionnaire consisted of five different approaches of error correction: repetiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The concept of attitude in language learning has therefore become a subject of interest for many ESL scholars (Abidin et al, 2012;Ahmed, 2015;Eshghinejad, 2016;Ibrahim,Yana & Yinusa, 2018;Karatas, Bademcioglu, & Ergin, 2016;Martinović, & Poljaković, 2011;Munir, 2015;Oroujlou & Vahedi, 2011;Smith, 1971). Although these studies share the subject of investigation (attitudes), they were conducted in different contexts.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of attitude in language learning has therefore become a subject of interest for many ESL scholars (Abidin et al, 2012;Ahmed, 2015;Eshghinejad, 2016;Ibrahim,Yana & Yinusa, 2018;Karatas, Bademcioglu, & Ergin, 2016;Martinović, & Poljaković, 2011;Munir, 2015;Oroujlou & Vahedi, 2011;Smith, 1971). Although these studies share the subject of investigation (attitudes), they were conducted in different contexts.…”
Section: Introductionmentioning
confidence: 99%
“…The teachers mostly use completion, asking for students to pause before continuing their speech, as elicitation. Unlike recast, elicitation is viewed as more effective in addressing students' errors (Behroozi & Karimnia, 2017). This study found that 90% of the use of elicitation can encourage responses from students.…”
Section: Teachers' Corrective Feedback Strategiesmentioning
confidence: 88%
“…Lately, a number of studies have been carried out to focus fully on teachers' error correction preferences in teaching second/foreign languages (Anggraeni, 2012;Behroozi & Karimnia, 2017;Jabu, Noni, Talib & Syam, 2017;Liskinasih, 2016;Motlagh, 2015;Suryoputro & Amaliah, 2016) or only students' error correction preferences (Alamri & Fawzi, 2016;Elçin & Öztürk, 2016;Fitriana, Suhatmady & Setiawan, 2016;Mungungu-Shipale & Kangira, 2017;Papangkorn, 2015;Park, 2010;Yoshida, 2008;Zhao, 2015). When these studies are compared, we see a noteworthy difference between what teachers and students show preference for.…”
Section: Literature Reviewmentioning
confidence: 99%